Regularities in Phenotypic Variation as a Property of the Developmental System: Evidence from the Evolution of Early Amphibians - Shishkin, M A (KnE Life Sciences, 2018)
An evident non-randomness in the variability of living organisms is caused by the integrity of their developmental systems, which undergo the evolutionary transformation as a whole. The commonest manifestation of such orderliness is the occurrence of homologous variations in related forms. The evolution of the dominant group of early amphibians (Temnospondyli) provides numerous examples of this phenomenon.